A Brief Overview of Health in Third-World Countries - Tsoromokos, Nikolaos; Kritikos, Panagiotis; Stefanou, Eva; Tsoromokos, Dimitrios (HAPSc Policy Briefs Series, 2025)
A significant global challenge continues to be health disparities in third-world countries, with them driven by economic, social, and environmental factors that limit access to quality healthcare. Economic inequalities and inadequate infrastructure, also known as structural inequalities or disparities, contribute to widespread health gaps, exacerbating the burden of non-communicable diseases, including infectious ones, as long as mental health disorders. In this brief, the key challenges faced by third-world healthcare systems and the comparison to European countries and their healthcare models will be examined, in addition to intersections of health, crime, and climate change. The need for policy interventions that prioritize equal healthcare access, mental health reforms, and climate resilience strategies is also considered in the brief. Recommendations are, lastly, provided to promote the extension of preventive care services, along with the integration of technology, accompanied by an improvement of international collaboration.